The structure of the catalytic domain of Tannerella forsythia karilysin reveals it is a bacterial xenolog of animal matrix metalloproteinases - Cerdà-Costa, Núria (2010)
Metallopeptidases (MPs) are among virulence factors secreted by pathogenic bacteria at the site of infection. One such pathogen is Tannerella forsythia, a member of the microbial consortium that causes peridontitis, arguably the most prevalent infective chronic inflammatory disease known to mankind. The only reported MP secreted by T. forsythia is karilysin, a 52-kDa multidomain protein comprising a central 18-kDa catalytic domain (CD), termed Kly18, flanked by domains unrelated to any known protein. We analyzed the 3D structure of Kly18 in the absence and presence of Mg(2+) or Ca(2+), which are required for function and stability, and found that it evidences most of the structural features characteristic of the CDs of mammalian matrix metalloproteinases (MMPs). Unexpectedly, a peptide was bound to the active-site cleft of Kly18 mimicking a left-behind cleavage product, which revealed that the specificity pocket accommodates bulky hydrophobic side chains of substrates as in mammalian MMPs. In addition, Kly18 displayed a unique Mg(2+) or Ca(2+) binding site and two flexible segments that could play a role in substrate binding. Phylogenetic and sequence similarity studies revealed that Kly18 is evolutionarily much closer to winged-insect and mammalian MMPs than to potential bacterial counterparts found by genomic sequencing projects. Therefore, we conclude that this first structurally-characterized non-mammalian MMP is a xenolog co-opted through horizontal gene transfer during the intimate coexistence between T. forsythia and humans or other animals, in a very rare case of gene shuffling from eukaryotes to prokaryotes. Subsequently, this protein would have evolved in a bacterial environment to give rise to full-length karilysin that is furnished with unique flanking domains that do not conform to the general multidomain architecture of animal MMPs.